Analisis Penerapan Sistem Informasi Akuntansi Sebagai Alat Pengendalian Dalam Pengelolaan Persediaan - Farah Nabilah; Nuramalia Hasanah; Aji Ahmad Sasmi (Jurnal Akuntansi, Perpajakan dan Auditing, 2025)
Inventory management is a crucial aspect for MSMEs, particularly in the food and beverage manufacturing sector, as it directly impacts operational smoothness and the accuracy of financial reports. This study aims to implement an accounting information system as an internal control tool for inventory management at the Freshking7 MSME. This research employed a qualitative method with a case study approach and the ADDIE development model. Data collection techniques included observation, interviews, documentation, and pre- and post-test questionnaires developed based on the Technology Acceptance Model (TAM). The findings indicate that prior to the implementation of written SOPs and flowcharts, inventory management faced issues such as inconsistent recording, weak internal control, delays in transaction recording, and discrepancies between physical inventory and system data. After implementing SOPs and flowcharts integrated with Mekari Jurnal and aligned with the COSO framework, inventory management became more structured, with improved user understanding and increased accuracy in inventory recording and monitoring. The study concludes that the implementation of an accounting information system supported by clear SOPs and flowcharts enhances internal control and inventory management effectiveness at Freshking7.